2013
DOI: 10.1021/nn4023119
|View full text |Cite
|
Sign up to set email alerts
|

Image-Guided Local Delivery Strategies Enhance Therapeutic Nanoparticle Uptake in Solid Tumors

Abstract: Nanoparticles (NP) have emerged as a novel class of therapeutic agents that overcome many of the limitations of current cancer chemotherapeutics. However, a major challenge to many current NP platforms is unfavorable biodistribution, and limited tumor uptake, upon systemic delivery. Delivery, therefore, remains a critical barrier to widespread clinical adoption of NP therapeutics. To overcome these limitations, we have adapted the techniques of image-guided local drug delivery to develop nano-ablation and nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 61 publications
0
48
1
Order By: Relevance
“…These dosages were chosen to approximate clinically relevant doxorubicin concentrations from previous chemoembolization studies (2325) and to be consistent with previous animal work on nanoablation (8), while attempting to create a range of concentrations for correlation analysis and to investigate a possible dose-response relationship.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…These dosages were chosen to approximate clinically relevant doxorubicin concentrations from previous chemoembolization studies (2325) and to be consistent with previous animal work on nanoablation (8), while attempting to create a range of concentrations for correlation analysis and to investigate a possible dose-response relationship.…”
Section: Methodsmentioning
confidence: 99%
“…Two minutes after DOX-SPIO injection, electroporation was applied to the tumor via a two-pronged electroporation tool (BTX, Holliston, MA) with two 0.4 mm-diameter needles separated by 1 cm, a configuration which has been shown to provide full coverage of the area between the electrodes (27). Eight 1300 V/cm pulses of 100 µs each with 100 ms between pulses were delivered with an ECM830 function generator (BTX, Holliston, MA) in accordance with previous work (8). The liver was then returned to the abdominal cavity, and the incision was closed via suture.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 While adapting the therapeutic techniques of interventional radiology, MRI-guided nanoparticle delivery could enhance uptake of an intratumoral agent and limit its nonspecific delivery to the reticuloendothelial system. 10,11 In support of this concept, some studies have reported on application of MRI-guided intra-arterial 12 and intrabiliary 13 nanoparticles for the treatment of liver tumors. Cell-penetrating peptides (CPPs) are short 30-residue synthetic peptides and represent one of the most promising strategies for enhancing the permeability of therapeutic agents, despite the limitations of various biomolecules with regard to extracellular and intracellular diffusion.…”
mentioning
confidence: 92%